PERAN SEKOLAH KRISTEN DALAM PENGEMBANGAN KARAKTER KRISTEN PADA SISWA - Alwinda Datu Kayang; Yuspina Tandi Sau', Wasti Azariya, Milka, Yuswandi (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research aims to investigate and analyze the role of Christian schools in shaping the Christian character of students through a case study approach. Education in Christian schools has a specific goal, namely to create a learning environment that reflects and integrates the values of the Christian religion into the daily lives of students. The primary focus of this research is on the role of teachers as role models and facilitators in the formation of Christian character, as well as the impact of religious activities on the development of the moral and spiritual aspects of students. The research method employs a qualitative approach with a case study design. Data is collected through in-depth interviews with teachers, school stafl, and students, as well as direct observations of religious activities at the school. Thematic data analysis is conducted to explore how the interaction between the components of Christian schools contributes to the formation of students' character. The results of the research are expected to provide in-depth insights into the role of Christian schools in the development of Christian character in students. The implications of this research include the potential application of eflective character education practices in Christian schools and contributions to further developments in the literature on Christian religious education.